Gap between Knowledge and Practice in Bio-Medical Waste Management in a Tertiary Care Centre - Nanjaiah, Ranjini; Lakshmana, Kusuma Maganur; Suresha (National Journal of Community Medicine, 2017)
Background: Health-care waste contains potentially harmful microorganisms which can infect hospital patients, health workers and the general public. Training and capacity building of health-care staff are essential in the efforts to minimize the transmission of secondary infections. Before beginning the process of creating awareness, it is first necessary to assess the knowledge and practices regarding biomedical waste management among nursing staff and its association with socio-demographic variables. Methods: This is an interview based cross sectional study involving 301 nursing staff working in tertiarycare hospitals. Results: Analysis of data showed that among 301 participants 91% were females and 9% were males, among the participants with good knowledge of biomedical waste disposal 93% were females and it is statistically significant with p value 0.005. Age and experience has impact on the proper biomedical waste disposal which is statistically significant with p value 0.019 and 0.013 respectively. Conclusions: Female staff nurse with more experience had better knowledge of health hazards of biomedical waste and proper disposal of waste and universal precautions.Health-care waste workers should be trained before starting work handling waste, and then on a routine basis (e.g. annually) to update their knowledge of prevention and control measures.